(3MGTjI Ydi TQM GdTeSjIs - (3GdLQLGfj, GdTQja, Ydj Hf eMeO Hf Ydj, J (B816 (3g`s ((3MSf Hf YHO GdQMef Hf CHj GdbGSe GdLKhejs)
(3ChdgG (B:s
(3HSe Gddg (B.. (3bhdg (B.. (3Ydi ebOeI hKdGK ebGdGJ hNGJeI gcPG hLO YHGQI (B.. (3ef GdfSN hGdUhGH Gf daX KdK gfG RjGOI hbYJ SghG ef bde GdfGSN jOd Ydi Pdc (B...s
(3BNQgG (B:s
... (3hgPG GdLhGH eQOhOg dGf GdTjN GdQFjS bO UQM (B.. (3HCf GdJUOjb HhLhO GdehVhY ef GdeHGOF GdJUOjbjI adG jchf CjVG (B..(3hbO JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5/7s
(3cTa GdXfhf (B2/1063 (3g`s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs